Inhibition of miR-4640-5p alleviates pulmonary hypertension in chronic obstructive pulmonary disease patients by regulating nitric oxide synthase 1 - Zhao Yang; Ping Li; Qun Yuan; Xi Wang; Hong-Hong Ma; Bing Zhuan (Respiratory Research, 2023)
Abstract Background Pulmonary hypertension (PH) is a devastating disease characterized by vasoconstriction and vascular remodeling, leading to right ventricular failure and death. PH is a common complication of chronic obstructive pulmonary disease (COPD). Accumulating evidence demonstrate that microRNAs participate in the pathobiology of PH in COPD patients. In this study, we aimed to evaluate the expression and function of microRNA-4640-5p (miR-4640-5p) in PH. Methods The mRNA and protein levels were determined by quantitative polymerase chain reaction (qPCR) and western blot, separately. Functional assays and western blot were performed to determine the effects of miR-4640-5p and NOS1 on cell growth, migration. Besides, the dual-luciferase reporter assays were used to validate miR-4640-5p and NOS1 interactions. Results We found that miR-4640-5p expression was significantly higher in the lung tissues of COPD-PH patients than in the healthy controls while higher expression of miR-4640-5p was correlated with more severe COPD-PH. By using pulmonary artery smooth muscle cell (PASMC) in in vitro assays, we demonstrated that inhibition of miR-4640-5p suppressed cell proliferation and migration of PASMC via regulating mTOR/S6 signaling. Bioinformatics analysis and validation experiments revealed that nitric oxide synthase 1 (NOS1) was a direct downstream target of miR-4640-5p. Overexpression of NOS1 partially antagonized the effect of miR-4640-5p in regulating PASMC cell proliferation and migration. In addition, our findings suggested that miR-4640-5p/NOS1 axis regulated mitochondrial dynamics in PASMCs. Furthermore, in the hypoxia-induced PH rat model, inhibition of miR-4640-5p ameliorated PH with reduced right ventricular systolic pressure and Fulton index. Conclusions miR-4640-5p regulates PH via targeting NOS1, which provides a potential diagnostic biomarker and therapeutic target for COPD-PH patients.